Interrelated adolescent-level food insecurity and common mental health disorders in Harari Region, Ethiopia: A cross-sectional study - Kasiye Shiferaw; Gari Hunduma; Yadeta Dessie; Tesfaye Assebe Yadeta; Biftu Geda; Negussie Deyessa (PLoS ONE, 2026)
Background Global adolescent-level food insecurity (AFI) and common mental disorders (CMD) represent a significant public health burden. While household-level food security is known to be associated with mental health disorders, there is a dearth of evidence regarding the specific association between AFI and CMDs in Ethiopia, particularly in the Harari Regional State. Methods A school-based cross-sectional study was conducted among 3,326 adolescents in the Harari Regional State, Eastern Ethiopia, utilizing a multistage sampling strategy stratified by locality and school type. Data were collected using validated scales adapted from previous studies, including the HFIAS for adolescent-level food insecurity, KIDSCREEN-10 for health-related quality of life, the Rosenberg Scale for self-esteem, and the SDQ-25 for CMDs. Data were collected using a structured questionnaire translated into Amharic and Afan Oromo and pre-tested for validity. A guided self-administration approach was employed by eight trained BSc nurses and psychiatric nurses. All data collectors and supervisors underwent rigorous training to ensure data quality. Questionnaires were subjected to daily checks for completeness during fieldwork, and double data entry was utilized for final validations and accuracy. Data were analysed using STATA version 16.1. Prior to analysis, data were screened for outliers, missing values, and normality. The structural equation model (SEM) demonstrated a good fit to the data (RMSEA = 0.03, CFI = 0.90, TLI = 0.89 and SRMR = 0.05), confirming the structural integrity of the model prior to the interpretation of path coefficients. We conducted SEM using maximum likelihood estimation after adjusting for relevant covariates. Results The descriptive results revealed that 14.50% of adolescents experienced moderate-to-severe food insecurity, while the prevalence of CMDs was 22.93%. Several factors were significantly associated with the prevalence of CMDs. AFI was linked to a higher likelihood of CMDs (β = 0.20, P < 0.001), as were substance use (β = 0.14, P < 0.001) and frequent financial difficulties (β = 0.06, P < 0.001). Conversely, higher quality of life (β = −0.07, P < 0.001) and stronger self-esteem (β = −0.06, P < 0.001) were associated with a lower likelihood of CMD symptoms. Furthermore, urban residency emerged as a protective factor, showing a significant negative association with CMDs (β = −0.21, P < 0.001). Conclusion AFI significantly predicts the occurrence of CMDs. A relationship is further driven by poor quality of life, diminished self-esteem, substance use, and financial instability. The study highlights the need for tailored interventions to tackle these functional drivers, suggesting that addressing food insecurity and its associated psychosocial factors is essential to reduce adolescents’ CMD burden.